Flexibilização procedimental e efetividade do processo - Rossini, Luiz Felipe (2018)
The present dissertation addresses the phenomenon of procedural flexibility, procedural technique which allows the acts and procedures to be adjusted to the peculiarities of the cause, providing the provision of effective judicial guardianship, assumption of the guarantee Constitutional access to justice. This research aims to establish the link between the procedural flexibility and the constitutional model of the process, as well as the vision of the process as an instrument for the realization of material law. To do so, we will look at the rule about stabilization, and the flexibilities admitted in our procedural system, either express or implied, in the search for the provision of fair, swift and effective judicial protection, being used in this research of the hypothetico-deductive method, and predominantly bibliographical research.